Water vapor condensation on substrates with nanoscale hydrophilic spots: A molecular dynamics study. (15th May 2023) - Wang, Zi-Jie; Wang, Shao-Yu; Wang, Dan-Qi; Yang, Yan-Ru; Wang, Xiao-Dong; Lee, Duu-Jong
Highlights: Vapor condensation on nanoscale hydrophilic spots is studied. The power of the growth curve is close to the theoretical value. The interaction between nucleated clusters reduces condensation performance. Increased spots number facilitate condensation but the marginal utility diminished. The edge effect disables small hydrophilic spots to attract water molecules. Abstract: Because of preferable nucleation and departure characteristics, hybrid wetting substrates have been widely used to enhance condensation. Nanoscale hydrophilic spots are expected to reduce the adhesive force between the droplet and substrate, thereby promoting droplet departure; however, whether such hydrophilic spots can enhance nucleation and cluster growth remains poorly understood. Using molecular dynamics simulations, this work studies vapor condensation on a hydrophobic background substrate decorated with nanoscale hydrophilic spots. The results show that on the substrate with larger isolated hydrophilic spots, a higher probability of vapor molecules colliding with hydrophilic spots leads to faster nucleation. In the growth stage, the time-evolved size and surface area of the cluster follow N ∼ t 3/2 and A ∼ t, respectively. With a fixed size of hydrophilic spots, increasing the hydrophilic spot density is found to enhance nucleation probability and increase the number of formed clusters; however, the competition between nucleation sites also suppresses the growth of individual clusters. Besides, an interesting phenomenon is observed that there is a critical size of hydrophilic spots below which vapor condensation cannot take place on the spots. This phenomenon can be explained by the fact that the hydrophobic atoms surrounding a hydrophilic spot weaken the affinity of the hydrophilic atoms that are located at the boundary of the hydrophilic spot, and thus reduce the interaction between the hydrophilic spot and vapor molecules. This edge effect will become extremely prominent if increasing the nucleation site number with a fixed hydrophilic atoms ratio. As a result, an appropriate nucleation site number should be designed to obtain the best condensation performance.